Giant Primary Neuroendocrine Neoplasms of the Liver: Report of 2 Cases With Molecular Characterization. (December 2019) - Pastrián, Laura G.; Ruz-Caracuel, Ignacio; Gonzalez, Raul S.
Primary neuroendocrine neoplasms of the liver have occasionally been reported in the liver, though many reports do not convincingly exclude metastases. In this article, we report 2 "giant" hepatic neuroendocrine lesions without evidence of a primary elsewhere after clinical workup. One occurred in a 21-year-old male; the lesion was a large cell neuroendocrine carcinoma measuring 24 cm. The patient died of disease in 10 months. The other occurred in a 25-year-old patient, was 18 cm wide, and was diagnosed as a well-differentiated neuroendocrine tumor, World Health Organization grade 3. The patient died of disease after 30 months. Molecular testing demonstrated only the presence of TP53 mutations in common. These cases expand our knowledge of seemingly primary neuroendocrine neoplasms of the liver, in particular, giant cases measuring more than 8 cm. Guidelines for clinical workup and therapy for these lesions remain unclear, but future thorough workup of such cases is necessary for specific characterization.